EVALUASI MANAJEMEN PASAR TRADISIONAL BERDASARKAN ASPEK PELAYANAN PRIMA (STUDI KASUS PASAR TRADISIONAL PETERONGAN SEMARANG) - Vinda Adeliana; Mohammad Agung Ridlo; Agus Rochani (Jurnal Planologi, 2017)
Efforts to control the management of traditional markets in terms of service excellence is expected to be carried out in synergy and more directed to the traders, buyers and market manager Peterongan. In His understanding of management's evaluation of traditional markets in terms of excellent service performed quantitative descriptive approach (quantitative approach) with a rationalistic approach. Through this approach, the researchers were able to find common ground as well as perceptions of a diverse range of different data. As a measure of evaluation used 6 main parameters, which include a) the effectiveness, b) efficiency, c) adequacy, d) equity, e) responsiveness, f) accuracy.      From the analysis conducted by researchers concluded that management is not optimal Peterongan market so that the evaluation results in terms of excellent service said to be "unfit". Especially in performing maintenance and care market, difficulties including costs and building maintenance program budget limited market and the lack of control of the market manager. On the other hand, the macro policy of the government is quite conducive to efforts to create traditional markets orderly, organized, safe, clean and healthy. Relating to matters that needed a more traditional markets to thrive and have a good competitiveness. In this case the performance of the government to manage Peterongan market should be improved to provide excellent service to traders and buyers.Keywords: Evaluation, Excellent Service, Traditional Market